2011
DOI: 10.1007/s00213-011-2336-y
|View full text |Cite
|
Sign up to set email alerts
|

A placebo-controlled study of sertraline’s effect on cortisol response to the dexamethasone/corticotropin-releasing hormone test in healthy adults

Abstract: Rationale The dexamethasone/corticotropin-releasing hormone (Dex/CRH) test is a neuroendocrine probe involving serial blood sampling of cortisol during a standardized pharmacological challenge without inducing psychological distress in humans. Some past studies in depressed patients have shown a “normalization” or decrease in cortisol response to the Dex/CRH test following successful treatment with an antidepressant. Studies in nondepressed healthy adult samples have also shown aberrant cortisol reactivity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…Similar results have been reported by Ising et al ( 2007 ), who demonstrated that patients who do not exhibit a reduction of the cortisol response to a dexamethasone/CRH test after 2–3 weeks of treatment are not likely to respond to the current treatment. However, this has not been confirmed in two other studies (Paslakis et al, 2010 ; Carpenter et al, 2011 ). For example, Carpenter et al ( 2011 ) rather found an increased pre-treatment cortisol after DEX/CRH to be associated with sertraline response.…”
Section: Predictors Of Poor Response To Antidepressant Therapy: Neuromentioning
confidence: 80%
See 1 more Smart Citation
“…Similar results have been reported by Ising et al ( 2007 ), who demonstrated that patients who do not exhibit a reduction of the cortisol response to a dexamethasone/CRH test after 2–3 weeks of treatment are not likely to respond to the current treatment. However, this has not been confirmed in two other studies (Paslakis et al, 2010 ; Carpenter et al, 2011 ). For example, Carpenter et al ( 2011 ) rather found an increased pre-treatment cortisol after DEX/CRH to be associated with sertraline response.…”
Section: Predictors Of Poor Response To Antidepressant Therapy: Neuromentioning
confidence: 80%
“…However, this has not been confirmed in two other studies (Paslakis et al, 2010 ; Carpenter et al, 2011 ). For example, Carpenter et al ( 2011 ) rather found an increased pre-treatment cortisol after DEX/CRH to be associated with sertraline response. Possibly, rapid initial improvement of the cortisol response following DEX/CRH would be a more effective predictor of response outcome.…”
Section: Predictors Of Poor Response To Antidepressant Therapy: Neuromentioning
confidence: 80%
“…The activation of HPA axis hypothesis considered that patients with depression activated pathological HPA axis excessively, which was closely associated with suicidal behavior of depression[27]. Antidepressant drugs such as serotonin reuptake inhibitors can inhibit the activation of HPA axis[28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Some acceptable mechanisms include the monoamine neurotransmitter hypothesis, the hypothalamic-pituitary-adrenal (HPA) axis activation hypothesis, nerve-inflammation hypothesis, cytokine hypothesis [3, 4, 5]. Antidepressant drugs such as serotonin reuptake inhibitors can inhibit the activation of HPA axis [6, 7]. However, long-term use antidepressant can cause lots of side effects.…”
Section: Introductionmentioning
confidence: 99%
“… 6 7 ] as well as in community populations [e.g. 8 9 ]. The IDS-SR also has been translated and cross-validated into 30 languages.…”
Section: Introductionmentioning
confidence: 99%